Drag the tiles to the correct boxes to complete the pairs. Not all tiles will be used. Consider the functions given below. SEE FILE ATTATCHED

Answer:
1. [tex] P(x) [/tex] ÷ [tex] Q(x) [/tex]---> [tex] \frac{-3x + 2}{3(3x - 1)} [/tex]
2. [tex] P(x) + Q(x) [/tex]---> [tex]\frac{2(6x - 1)}{(3x - 1)(-3x + 2)}[/tex]
3. [tex] P(x) - Q(x) [/tex]---> [tex] \frac{-2(12x - 5)}{(3x - 1)(-3x + 2)} [/tex]
4. [tex] P(x)*Q(x) [/tex] --> [tex] \frac{12}{(3x - 1)(-3x + 2)} [/tex]
Step-by-step explanation:
Given that:
1. [tex] P(x) = \frac{2}{3x - 1} [/tex]
[tex] Q(x) = \frac{6}{-3x + 2} [/tex]
Thus,
[tex] P(x) [/tex] ÷ [tex] Q(x) [/tex] = [tex] \frac{2}{3x - 1} [/tex] ÷ [tex] \frac{6}{-3x + 2} [/tex]
Flip the 2nd function, Q(x), upside down to change the process to multiplication.
[tex] \frac{2}{3x - 1}*\frac{-3x + 2}{6} [/tex]
[tex] \frac{2(-3x + 2)}{6(3x - 1)} [/tex]
[tex] = \frac{-3x + 2}{3(3x - 1)} [/tex]
2. [tex] P(x) + Q(x) [/tex] = [tex] \frac{2}{3x - 1} + \frac{6}{-3x + 2} [/tex]
Make both expressions as a single fraction by finding, the common denominator, divide the common denominator by each denominator, and then multiply by the numerator. You'd have the following below:
[tex] \frac{2(-3x + 2) + 6(3x - 1)}{(3x - 1)(-3x + 2)} [/tex]
[tex] \frac{-6x + 4 + 18x - 6}{(3x - 1)(-3x + 2)} [/tex]
[tex] \frac{-6x + 18x + 4 - 6}{(3x - 1)(-3x + 2)} [/tex]
[tex] \frac{12x - 2}{(3x - 1)(-3x + 2)} [/tex]
[tex] = \frac{2(6x - 1}{(3x - 1)(-3x + 2)} [/tex]
3. [tex] P(x) - Q(x) [/tex] = [tex] \frac{2}{3x - 1} - \frac{6}{-3x + 2} [/tex]
[tex] \frac{2(-3x + 2) - 6(3x - 1)}{(3x - 1)(-3x + 2)} [/tex]
[tex] \frac{-6x + 4 - 18x + 6}{(3x - 1)(-3x + 2)} [/tex]
[tex] \frac{-6x - 18x + 4 + 6}{(3x - 1)(-3x + 2)} [/tex]
[tex] \frac{-24x + 10}{(3x - 1)(-3x + 2)} [/tex]
[tex] = \frac{-2(12x - 5}{(3x - 1)(-3x + 2)} [/tex]
4. [tex] P(x)*Q(x) = \frac{2}{3x - 1}* \frac{6}{-3x + 2} [/tex]
[tex] P(x)*Q(x) = \frac{2*6}{(3x - 1)(-3x + 2)} [/tex]
[tex] P(x)*Q(x) = \frac{12}{(3x - 1)(-3x + 2)} [/tex]
Composite functions involve combining multiple functions to form a new function
The functions are given as:
[tex]P(x) = \frac{2}{3x - 1}[/tex]
[tex]Q(x) = \frac{6}{-3x + 2}[/tex]
[tex]P(x) \div Q(x)[/tex] is calculated as follows:
[tex]P(x) \div Q(x) = \frac{2}{3x - 1} \div \frac{6}{-3x + 2}[/tex]
Express as a product
[tex]P(x) \div Q(x) = \frac{2}{3x - 1} \times \frac{-3x + 2}{6}[/tex]
Divide 2 by 6
[tex]P(x) \div Q(x) = \frac{1}{3x - 1} \times \frac{-3x + 2}{3}[/tex]
Multiply
[tex]P(x) \div Q(x) = \frac{-3x + 2}{3(3x - 1)}[/tex]
Hence, the value of [tex]P(x) \div Q(x)[/tex] is [tex]\frac{-3x + 2}{3(3x - 1)}[/tex]
P(x) + Q(x) is calculated as follows:
[tex]P(x) + Q(x) = \frac{2}{3x - 1} + \frac{6}{-3x + 2}[/tex]
Take LCM
[tex]P(x) + Q(x) = \frac{2(-3x + 2) + 6(3x - 1)}{(3x - 1)(-3x + 2)}[/tex]
Open brackets
[tex]P(x) + Q(x) = \frac{-6x + 4 + 18x - 6}{(3x - 1)(-3x + 2)}[/tex]
Collect like terms
[tex]P(x) + Q(x) = \frac{18x-6x + 4 - 6}{(3x - 1)(-3x + 2)}[/tex]
[tex]P(x) + Q(x) = \frac{12x - 2}{(3x - 1)(-3x + 2)}[/tex]
Factor out 2
[tex]P(x) + Q(x) = \frac{2(6x -1)}{(3x - 1)(-3x + 2)}[/tex]
Hence, the value of P(x) + Q(x) is [tex]\frac{2(6x -1)}{(3x - 1)(-3x + 2)}[/tex]
P(x) - Q(x) is calculated as follows:
[tex]P(x) - Q(x) = \frac{2}{3x - 1} - \frac{6}{-3x + 2}[/tex]
Take LCM
[tex]P(x) - Q(x) = \frac{2(-3x + 2) - 6(3x - 1)}{(3x - 1)(-3x + 2)}[/tex]
Open brackets
[tex]P(x) - Q(x) = \frac{-6x + 4 - 18x +6}{(3x - 1)(-3x + 2)}[/tex]
Collect like terms
[tex]P(x) - Q(x) = \frac{-18x-6x + 4 + 6}{(3x - 1)(-3x + 2)}[/tex]
[tex]P(x) - Q(x) = \frac{-24x +10}{(3x - 1)(-3x + 2)}[/tex]
Factor out -2
[tex]P(x) - Q(x) = \frac{-2(12x -5)}{(3x - 1)(-3x + 2)}[/tex]
Hence, the value of P(x) - Q(x) is [tex]\frac{-2(12x -5)}{(3x - 1)(-3x + 2)}[/tex]
P(x) * Q(x) is calculated as follows:
[tex]P(x) \times Q(x) = \frac{2}{3x - 1} \times \frac{6}{-3x + 2}[/tex]
Multiply
[tex]P(x) \times Q(x) = \frac{12}{(3x - 1)(-3x + 2)}[/tex]
Hence, the value of P(x) * Q(x) is [tex]\frac{12}{(3x - 1)(-3x + 2)}[/tex]
Read more about composite functions at:
https://brainly.com/question/10687170